PEMBENIHAN NILA MERAH (Oreochromis sp.) MENGGUNAKAN JARING APUNG DI WADUK KEDUNGOMBO - Rustadi Rustadi; Djumanto Djumanto; Bambang Triyatmo; Ign. Hardaningsih; Hery Saksono (Jurnal Perikanan Universitas Gadjah Mada, 1996)
The objectives of the research were to know the production of hatchery, survival rate and growth rate of fry. Floating nets  were made for plastics hapa (2 mm mesh size) with 3 different size (5 m2, 10 m2, and 15 m2). The larvae were stocked in different hapa nursery size ( 1 m3, 2 m3, 3 m3) at the rate of 1000 larvae/m3 of water. The fry produced from the first nursery were subsequently reared in waring (mesh size 0,04 cm) at density of 600 fry/m3 of water. The spawning were conducted for 6 months, while larvae rearing were 2 months for each period respectively. The result showed that the hatchery of 15 m2 scale were technically and biologically feasible. During 6 months period it produced 11,870 fingerling of 40 gram, 3,028 fry of 4 gram and 4,290 of larvae. The survival rate and growth rate of fry water not significantly affected by different hapa size either in the first and second nursery. The survival rate of the first nursery was 64.70-72.63% of 5.0-6.8 cm fry, while the second nursery was 97.29-98.30% of 11.5-12.4 cm fry.